SWOT Analysis of MSMe Business Strategy: A Critical Approach to Digital Transformation and Industrial Competitiveness - hafiz, Achmad Al-Hafiz Lubis; Marliyah, Marliyah; Syahbudi, Muhammad (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This study examines the development strategy of ornamental fish cultivation from an Islamic economic perspective, with a case study of Naga Aquatic in Medan City. The research aims to analyze how business strategies can align with Islamic principles while enhancing competitiveness and sustainability in the ornamental fish sector. Methods A qualitative descriptive approach was employed, using interviews, field observations, and document analysis to collect data from the owner and operators of Naga Aquatic. SWOT analysis was applied to evaluate internal and external strategic factors. Results: The findings reveal that Naga Aquatic possesses strong internal strengths including diverse and appealing fish varieties, reputable branding, and growing market demand despite external threats such as intense competition and seasonal disease risks. The business scored 2.877 on the Internal Factor Evaluation (IFE) and 2.951 on the External Factor Evaluation (EFE), positioning it in Quadrant I of the IE Matrix. This reflects a favorable strategic position for aggressive growth Conclusion and suggestion: To capitalize on this position, S–O strategies are recommended, including digital promotion, product diversification, collaboration with local fisheries, and the development of derivative product lines. These strategies are not only market-oriented but also consistent with Islamic business ethics, promoting halal entrepreneurship, community empowerment, and ethical business conduct.